THE METHOD OF MATHEMATICAL INDUCTION IN PROVING IDENTITIES (Global Conference on Multidisciplinary Research and Innovation, 2026)
Many problems in mathematics are related to proofs, and such problems can be solved using various methods: elementary methods, using properties, and the method of mathematical induction. Depending on the formulation of the problem, each of these methods may offer different levels of convenience.